Tumor‐Activatable Nanoparticles Target Low‐Density Lipoprotein Receptor to Enhance Drug Delivery and Antitumor Efficacy. Issue 24 (24th June 2022) - Jiang, Xiaomin; Han, Wenbo; Liu, Jianqiao; Mao, Jianming; Lee, Morten J.; Rodriguez, Megan; Li, Youyou; Luo, Taokun; Xu, Ziwan; Yang, Kaiting; Bissonnette, Marc; Weichselbaum, Ralph R.; et al.
Abstract: The binding of plasma proteins to nanomedicines is widely considered detrimental to their delivery to tumors. Here, the design of OxPt/SN38 nanoparticle containing a hydrophilic oxaliplatin (OxPt) prodrug in a coordination polymer core and a hydrophobic cholesterol‐conjugated SN38 prodrug on the lipid shell for active tumor targeting is reported. OxPt/SN38 hitchhikes on low‐density lipoprotein (LDL) particles, concentrates in tumors via LDL receptor‐mediated endocytosis, and selectively releases SN38 and OxPt in acidic, esterase‐rich, and reducing tumor microenvironments, leading to 6.0‐ and 4.9‐times higher accumulations in tumors over free drugs. By simultaneously crosslinking DNA and inhibiting topoisomerase I, OxPt/SN38 achieved 92–98% tumor growth inhibition in five colorectal cancer tumor models and prolonged mouse survival by 58–80 days compared to free drug controls in three human colorectal cancer tumor models without causing serious side effects. The study has uncovered a novel nanomedicine strategy to co‐deliver combination chemotherapies to tumors via active targeting of the LDL receptor. Abstract : The core‐shell nanoparticle that containing a hydrophilic oxaliplatin prodrug in a coordination polymer core and a hydrophobic cholesterol‐conjugated SN38 prodrug on the lipid shell for active tumor targeting is developed. This tumor‐activable nanoparticle hitchhikes on low‐density lipoproteins, concentrates in tumors via LDL receptor‐mediated endocytosis, and selectively releases oxaliplatin and SN38 in lysosome, resulting superior antitumor effects.